Late conversion: The impact of professionalism on European rugby union - Vincent Hogan; Patrick Massey; Shane Massey (University College Dublin, UCD School of Economics, 2011)
Rugby union only went professional in 1995, much later than other major team sports resulting in major changes in league structures. Different arrangements regarding revenue sharing and salary caps between the three main European rugby leagues provides an opportunity to test the impact of such factors on competitive balance. The paper also considers the issue of competitive balance between leagues based on performances in European competitions. It has been argued that soccer's rules which require leagues to operate along national lines increased competitive imbalance at both national and European level. Rugby provides an interesting comparison as it has no such restrictions.
Keywords: D02; D21; D23; K21; L14; L22; L23; L83; 330; Professional team sports; competitive balance; league structures; Coase Theorem; collective selling; broadcast rights; salary caps